Catalytic Upgrading of Phenolic Oil by Etherification with Methanol. Issue 10 (8th September 2016) - Wang, Ze; Dang, Dan; Lin, Weigang; Song, Wenli
Abstract: Catalytic etherification of phenolic oil with methanol was investigated to decrease the polarity and acidity of the product oil. The catalyst KH2 PO4 /activated alumina (AA) provided the best performance due to its excellent dehydration and anti‐coking property. When catalyzed by KH2 PO4 ‐AA, the content of aryl ethers increased with rising temperature during the early stage but decreased at 500 °C. Alkoxy phenols had an inhibiting effect on etherification of alkyl phenols due to adsorption competition. Aryl ethers were mostly generated from alkyl phenols, while alkoxy phenols also contributed by simultaneous conversion to dialkoxybenzenes and diphenols, with a higher selectivity to diphenols. This explained the reduced alkoxy phenols and more generated alkyl phenols and aryl ethers at 350 °C. Abstract : Upgrading of phenolic oil by etherification with methanol using potassium salts supported by activated alumina (AA) as catalysts was investigated in order to reduce the polarity and acidity of the product oil. The catalyst KH2 PO4 ‐AA exhibited the best performance due to its dehydration and anti‐coking property. Alkoxy phenols exerted an inhibiting effect on etherification of alkyl phenols.